Design and development of plasma CNC machine structure (plate) - Mohd Hamka, Mohd Jaapar (2013)
Computer Numerical Control (CNC) machines are used in a variety of ways in supporting the development of new products and processes and can provide an excellent means to expose students to standardized control procedures as well as offer opportunities to effectively supplement the teaching of control systems and instrumentation. Using Mach3 for software control and stepper motors for power transmission, a relative low cost but effective CNC Plasma machine was developed by Western Carolina University (WCU) and Asheville-Buncombe Technical Community College through a joint partnership. This paper will present a logical approach to developing such a system and describe how applications have been integrated into curricula at both the two-year and university level programs through Project Based Learning (PBL). Educational merit and approaches will be described relative to respective educational levels.